پاکستانی معاشرہ میں عدم برداشت اور تشدد کے رجحانات:مقاصد شریعہ کی روشنی میں تجزیاتی مطالعہ: Trends of intolerance and violence in Pakistani society: Analytical Study in the light of the objectives of Sharia (Al-Aasar, 2025)
We relate to the religion of Islam, and Islam is a religion that guarantees the protection of life, property, honor and dignity of not only Muslims, but also all people, irrespective of their religion and race. The essence of Islam is salam, which means peace, and without a doubt, Islam is the bearer of peace and security, as exemplified by the saying of the Prophet of Islam, "A Muslim is one from whose hand and tongue other Muslims are safe." Our religion teaches us to reject intolerance and violence in our behavior and advises us to deal with all matters with tolerance and patience. The scholars of Islam discovered the objectives of the Islamic Sharia after much persuasion, careful study and research of the Qur'an and the Sunnah, so that these objectives of the Sharia should be taken into account when proposing solutions to the problems in the society. Generally, they are divided into five objectives, which include protection of religion, protection of self, protection of honor, protection of property, protection of race. In the paper under consideration, keeping in mind these objectives of Sharia, to prevent intolerance and violent attitudes in the society, So that a peaceful Islamic welfare society can be established.